ANALISIS KETIDAKTERISIAN DIAGNOSIS PASIEN RAWAT INAP DI LEMBAR RINGKASAN MASUK DAN KELUAR (RMK) DAN RESUME MEDIS RSKIA PKU MUHAMMADIYAH KOTAGEDE - , AYU FITRIYATI; , Eddy Kristiyono, A.Md. PerKes., SKM. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Diagnosis is an important data that must be documented in the medical record entry summary sheet is mainly an admission/discharge and a sheet of discharge summary. The usefulness of documenting the diagnosis in one of the two pieces to ensure continuity of medical services with high quality and useful material for doctors who accept these patients when treated back in the hospital, sources of data report generation, and the basis for setting rates health insurance claims. In RSKIA PKU Muhammadiyah Kotagede still there not filled documentation diagnosis resulting data sources only report the register book. Goals: this study was to analyze not filled inpatient diagnosis and determine the factors. Methods: This research uses descriptive research techniques with a qualitative approach. Sample objects used were 171 inpatient medical record file summary sheet admission/discharge and discharge summary the final quarter of 2013 with a random sample techniques are used while the sample is subject medical records officers, amounting to 3 people, 3 doctors, 2 nurses, and 1 midwife with a purposive sample technique. Result: There not filled diagnosis inpatients at admission/discharge sheet of 23.98% and 35.67% for summary discharge. Not filled diagnosis in admission/discharge sheets and summary discharge largely derived from patients hospitalized in general pediatric wards. Cause not filled diagnosis inpatients at admission/discharge sheet and summary discharge is a man of factors, methods and money. Man factor is less responsible doctors, nurses and midwives do not always check the completeness of the medical record and not remind doctors and medical recorder does not perform the analysis of medical record file